Kriss Romaní as transnational legal system - Rojas Venegas, Claudia Andrea (2008)
The Romani Kriss or Romaniya is the transnacional legal system of rom (gypsy) people. The system application of rights among rom is called Kriss, expression that designates the common right as well as the meeting or council of elders in charge of carrying it out. This article analy- ses and describes the process of rom people’s organization based on the right of administering justice under their own cultural patterns. Dynamics developed in Latin America are looked over, specially those cases in Colombia and Chile